(untitled) (Performance, Religion, and Spirituality, 2024)
Creole Religions of the Caribbean from Vodou and Santería to Obeah and Espiritismo: An Introduction by Margarite Fernàndez Olmos and Lizabeth Paravisini-Gebert (Edmund Lingan); Puppet and Spirit : Ritual, Religion, and Performing Objects. Volume I Sacred Roots : Material Entities, Consecrating Acts, Priestly Puppeteers edited by Claudia Orenstein and Tim Cusack (Pallama Ghosh)